INDISCRIMINATE USE OF GLP-1 ANALOGUES, SUCH AS SEMAGLUTIDE (OZEMPIC®), FOR AESTHETIC PURPOSES AND MULTIDISCIPLINARY ACTION IN CARE AND RISK PREVENTION - de Morais Filho, Valdemar Mendes; Melo, Gisele Wevely de Souza; Oliveira, Janainna Rocha Batista; Martins, Cleonice Lucia; Vasconcelos, Vania do Socorro Rodrigues; de Avelar, Arinea Avelar; Santos, Julio Gladston Ribeiro; Alves, Marilia Emanuele Modesto; Ferreira, Maísa de Aquino Campos; de Moraes, Junicimeira Lemos; Santos, Wesley de Jesus; Santos, Izabel Fiel; et al. (Editora Impacto Científico, 2025)
The use of glucagon-like peptide-1 (GLP-1) receptor agonists, such as semaglutide, has expanded significantly beyond approved clinical indications, increasingly being used by young and healthy individuals for aesthetic weight loss purposes. This chapter presents an integrative literature review on the clinical effects, associated risks, ethical and social implications of off-label use of these medications, highlighting the role of the multiprofessional team in preventing harm and promoting patient safety. Analysis of recent studies shows significant efficacy in weight reduction and metabolic improvement, but also identifies important risks, including gastrointestinal adverse effects, pancreatitis, renal alterations, eating disorders, and negative psychological impacts. The chapter emphasizes the integrated role of physicians, nurses, pharmacists, nutritionists, physiotherapists, and psychologists in patient assessment, monitoring, education, and support. It concludes that rational and safe use of GLP-1 agonists depends on clinical supervision, ethical approach, and educational strategies, aiming to balance therapeutic efficacy and patient safety.DOI: https://doi.org/10.56238/edimpacto2025.060-023